PENGARUH KUALITAS PELAYANAN DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PADA CAFE KOPI SIIPPP DI SITUBONDO DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Mawadah, Imfitahol; Ediyanto, Ediyanto; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2022)
The influence of service quality on determining purchasing at the cafÃ© kopi siippp with consumer confidance as an intervening variable. Imfitahol mawadah. Nim. 201813033, 2022, 64: page Departement of manajemen and business universitas abdurachman saleh situbondo. The The purpose of this study is to analyze the variable the influence of service quality on determining purchasing at the cafÃ© kopi siippp with consumer confidance as an intervening variable. Using the structural equation model partial least square PLS. The results of hypothesis testing have a direct effect using the smart PLS 3.0 application. Service quality has a significant effect on consumer confidance, H1 accepted, service quality has a significant effect on determining purchasing H2 accepted, consumer confidance has a significant effect on determining purchasing H3 accepted, and service quality has a significant effect on determining purchasing through consumer confidance H4 accepted